Doświadczenia z projektowania i wdrażania Zrównoważonej Karty Wyników w Przedsiębiorstwie Budowy Kopalń PeBeKa SA - Rybak, Lech (Preparation and Implementing of the Balanced Scorecard in Przedsiebiorstwo Budowy Kopaln PeBeKa SA, 2006)
The preparation and implementing of the Balanced Scorecard is the project which can be treated as a special one because it is not possible to establish the result of it at the starting moment. Moreover, the "material" of the input - business strategy - can be deeply changed during the period of such a project. So the project team faces the big challenge how to reach the find result in the conditions of such high entropy of the system. Experiences in this field reached during the common project based on team works of IDS Scheer Plant Polska Sp. z o.o. and Przedsiębiorstwo Budowy Kopaln PeBeKa SA w Lubinie are the framework of this paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 500-510